ESTUDO DA DEFORMAÇÃO CRIOGÊNICA DE ALUMÍNIO, COBRE E PRATA - Maeda, Milene Yumi (2017)
Commercially pure aluminum, copper and silver samples were rolled at room and cryogenic temperatures until approximately 99% of thickness total reduction, causing deformation (ε) between 3.93 and 4.61 Although not in balance state, the metals tend to have more defects density when cryo rolled, especially higher dislocation density, evidenced by calculations based on X-ray data for copper and silver. Higher defects density implies superior hardness, tensile strength limit and yield strength, but smaller elongation. There was evidence of stacking fault energy (SFE) influence in the process, evaluating hardness and properties obtained through tensile tests of the materials. The cryogenic temperature (CT) and room temperature (RT) rolled samples were evaluated by hardness tests, tensile tests, scanning electron microscopy (SEM) and X-ray diffraction (XRD), which indicate influence of stacking fault energy (SFE) on process. The hardness of all the materials tend to drop when they are kept at RT after cryo rolling and bigger larger hardness decrease was observed for silver, which one has the lowest SFE and slightest hardness decreased was noticed for aluminum, which has high SFE. There is evidence that cryo rolling is more attractive for low SFE materials after ageing at RT, as long as silver presented simultaneous increase in higher tensile strength of about 53% and 29% gain of elongation when compared to the same one rolled at RT. Elongation gain of silver can be associated to static recrystallization, as evidenced contrasting silver’s tensile charts after ageing and recrystallized silver. In turn, copper presented 15% of strength limit increase and just 5% elongation, whereas aluminum had both strength limit and elongation reduced.